Research on the consequences of employees’ unethical pro-organizational behavior: The moderating role of moral identity - Zhao, Manlu; Qu, Shiyou (Frontiers in Psychology, 2022)
In recent years, employees’ unethical pro-organizational behavior (UPB) has become a social hot issues. This behavior benefits their organization or colleagues, while violating core social ethics. However, numerous studies predominately focus on identifying its antecedents and the formation mechanisms. There are only a few studies focused on the effects and outcomes of UPB. Moreover, guilt triggered by unethical behaviors can motivate individuals to adopt pro-social behaviors, but the studies on the effects of UPB on pro-social behavior of actors are rather limited. Based on the conservation of resources theory, this paper explores the underlying relationship of employees’ unethical pro-organizational behavior on their own pro-environmental behavior. Through collecting data (N = 319) from an online survey company in China at different times, this study found that employees’ UPB is negatively related to their own pro-environmental behavior, mediated via feelings of guilt. Meanwhile, the moderating roles of moral identity was investigated within this relationship, which can moderate the indirect relationship between employees’ UPB and pro-environmental behavior through guilt. This study aims to clarify the effect mechanism of employees’ unethical pro-organizational behavior, and this paper disscussed theoretical and practical implications of these findings.